Selective Hydrogenation of Furfural in a Proton Exchange Membrane Reactor Using Hybrid Pd/Pd Black on Alumina. Issue 22 (11th October 2019) - Carl, Sarah; Waldrop, Krysta; Pintauro, Peter; Thompson, Levi T.; Tarpeh, William A.
Abstract: Conventional thermocatalytic hydrogenation employs high temperatures and pressures and often exhibits low selectivity toward desired products. Electrochemical hydrogenation can reduce energy input by operating at ambient conditions and improving process control and selectivity; however, electrocatalysts face stability and conductivity limitations. To overcome these obstacles, we physically mixed a traditional electrocatalyst (Pd black) with a hydrogenation‐active metal (Pd) supported on a conventional metal oxide support (alumina, Al2 O3 ) and investigated electrochemical hydrogenation of furfural, a model biomass compound. Experiments were conducted in a proton exchange membrane (PEM) reactor, in which synthesized electrocatalysts were used as cathodes. Catalysts with Pd black and varying loadings of Pd on Al2 O3 were used to determine the impact of hydrogen spillover on electrocatalytic hydrogenation mechanisms, selectivity, and rates. Observed hydrogenation rates and selectivities were linked to structural and compositional properties of the catalyst mixtures. Of the Pd black cathodes tested, 5 wt % Pd/Al2 O3 exhibited production rates as high as pure Pd black and higher selectivity towards completely hydrogenated products. Improved selectivity and rates were attributed to a synergistic interaction between Pd black and 5 wt % Pd/Al2 O3 in which Pd/Al2 O3 increased the number of active sites, while Pd black provided stable conductivity. Abstract : Breaking away from convention : The performance of hybrid cathodes, consisting of a traditional electrocatalyst (Pd black) with a hydrogenation‐active metal (Pd) supported on a conventional metal oxide support (Al2 O3 ), is investigated using electrochemical hydrogenation of furfural in a proton exchange membrane reactor. Varying loadings of Pd on Al2 O3 within the hybrid cathode elucidates the impact of structural and compositional properties of the catalyst mixtures on hydrogenation rates and selectivities.